Innovation, competitive strategy and MSME performance: a survey study on culinary SMEs in Indonesia during the COVID-19 pandemic - Pusung, Cancelyn Shearin; Narsa, Niluh Putu Dian Rosalina Handayani; Wardhaningrum, Oktaviani Ari (Business: Theory and Practice, 2023)
The aim of this research is to examine the relationship between innovation and performance in culinary sector MSME in Indonesia. This research also examines the mediating role of competitive strategies on the correlation of innovation in SME performance. This study proceeds using a quantitative approach and Partial Least Square (PLS) through SmartPLS software. The sample of this study consisted of 201 SMEs in Indonesia (specially in Surabaya) that engage in the food and beverage (culinary) sector, and the researcher used an accidental sampling technique to collect data. The result revealed that process innovation was directly, positively, and significantly related to the performance of SMEs. Furthermore, the analysis found that competitive strategies, including cost leadership, differentiation, and focus, mediated a partial relationship between innovation and SME performance and had a full mediation of innovation in SME performance. This study shows that SMEs with process innovation can more easily achieve superior performance than SMEs which implement product-oriented innovation. This research focused on SMEs in Surabaya, so it is necessary to be careful in generalizing the results to other locations or business sectors.